The place of corporate culture in human resources management and an example - Bilgin, Sema (My University, 2005)
Name and Surname: Sema Bilgin Field: Public Administration Programme: Human Resources Management and Development Supervisor: Assistant Professor Ahmet Tuğrul Savaş Degree Awarded and Date: Master - January 2005 Corporate Culture, Human Resources Management

THE PLACE OF CORPORATE CULTURE IN HUMAN RESOURCES MANAGEMENT AND AN EXAMPLE In today's business world the competition is very dense by the effect of globalization. Organizations have to create differences for struggle by competition. One of the differences that organizations have to create is to turn into an institution by values that fit to the organization. In the way of institution process organizations create their own values and they hope from their employees to share their values. This is the process of creating corporate culture. In this process Human Resources Management direct their procedures according to corporate culture. In this thesis we looked the process of creating corporate culture by literature review. We also analyzed the interaction of Human Resources Management with this process. And we gave an example by descriptive research technique which is the method of qualitative researh. And this example is chosen from the ''Next 500 Major Industrial Enterprises of Turkey 2003 Research'' which is made by İstanbul Chamber of Industry. We chosed this example because of it is one of the 10 foundation of this research which supported our theory section. Soyadı: Sema Bilgin Kamu Yönetimi Human Resources Management and Development Yrd. Doç. Dr. Ahmet Tuğrul Savaş Tez Türü ve Tarihi: Yüksek Lisans - Ocak 2005 Kurum Kültürü, İnsan Kaynakları Yönetimi ÖZET KURUM KÜLTÜRÜNÜN İNSAN KAYNAKLARI YÖNETİMİNDEKİ YERİ VE BİR ÖRNEK Günümüzde globalleşmenin etkisiyle artan rekabet ortamında geride kalmamak adına işletmeler çeşitli şekillerde farklılık yaratma çabasındadırlar. Bu çabalardan bir tanesi oturmuş değerler bütünü çerçevesinde kurumsallaşma çabasıdır. Kurumsallaşma yolunda ilerlerken, bir taraftan işletme değerleri belirlenir ve diğer taraftan bu değerlerin bütün çalışanlar tafarından paylaşılması beklenir. İşte bu süreç kurum kültürü yaratma sürecidir. Bu süreçte İnsan Kaynakları Yönetimi kurum kültürüne göre politikalarına yön verir. Biz bu çalışmada kurum kültürü oluşum sürecine literatür taramasıyla bakarken bu sürecin İnsan Kaynakları Yönetimiyle etkileşimini inceledik ve Nitel Araştırma Yöntemlerinden biri olan Tanımlayıcı (Betimsel) Analiz metodu kullanarak bir örnek verdik. Bu örneği, İstanbul Sanayi Odasının ''Türkiyenin İkinci 500 Büyük Sanayi Kuruluşu 2003'' araştırmasında ilk 10 daki işletmelerden biri olduğu ve çalışmamızın teori bölümünü desteklediği için seçtik.
Keywords: İnsan Kaynakları Yönetimi; Kurum Kültürü; Şirketler